The child protection policy in North Macedonia: Perceptions of professionals and beneficiaries - Kunovska, Elizabeta (Ревија за социјална политика/Journal of Social Policy, 2023)
Social and child protection is a set of policies and programs designed to reduce and prevent poverty, vulnerability, and social exclusion throughout the life cycle. Early childhood interventions provide an exceptional opportunity to invest in something that is both cost-effective and reasonable, cost-effective in the sense that there is an opportunity to obtain a skilled and capable workforce in the future, and fair in the sense that this intervention gives the best results for children who live in un- favourable conditions and lack adequate stimulation. The paper aims to analyse the perception of the professionals and beneficiaries regarding needs for enhancementof the child protection system in North Macedonia. The practical goal of this study is for the results to serve as guidelines for evidence-based policy making, as well as the introduction of new programs or the improvement of existing ones.
Keywords: Child protection; social protection; child and social protection reform; human capital; early-childhood development; early interventions; schhool readiness; capacity building; equity